Highly Oriented Bio‐Mimetic Hydrogels by Calendering - Zhanqi Liu; Yuqing Wang; Haidi Wu; Huamin Li; Longcheng Tang; Guo Wang; Daxin Zhang; Jianping Yin; Yinggang Miao; Yongqian Shi; Pingan Song; An Xie; et al. (Advanced Science)
Abstract Anisotropic hydrogels are promising candidates as load‐bearing materials for tissue engineering, while huge challenges remain in exploring effective and scalable methods for the preparation of anisotropic hydrogels with simultaneous high tensile strength, large toughness, good fracture strain, excellent fatigue and swelling resistances. Inspired by the brick‐and‐mortar layered structure of nacre and the hierarchical fibril strucure of soft tissues (e.g., tendon and ligament), a facile organogel‐assissted calendering strategy is reported to design anisotropic hydrogels with a highly oriented and dense fiber lamellar strucure. The synergy of shearing and annealing promotes macromolecular chain alignment and crystallinity along the calendering direction while forming a nacre‐like lamellar morphology in the thickness direction. The tensile strength, elastic modulus, toughness and fracture energy of the anisotropic hydrogels can reach as high as 41.0 ± 6.4 MPa, 67.0 ± 5.1 MPa, 46.2 ± 3.3 MJ m−3, and 62.20 ± 8.55 kJ m−2, respectively. More importantly, the hydrogels show excellent crack growth and swelling resistances with the fatigue threshold increased to 2170 J m−2. This study provides a promising approach for fabrication of large‐sized biomimetic anisotropic hydrogels with outstanding mechanical properties for biomedical and engineering applications.